Bahamas. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2015)
The main activities carried out by the Institute in the Bahamas during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as aquaculture, egg production, livestock, marketing, agricultural development, veterinary medicine, food processing, plant health, health animal, through the Codex Alimentarius. Finally, it was supported by the inclusion of international standards, gender equality, inclusion of artisan women and pest control, such as black sigatoka.